Use of Computing Platforms of General Purpose as a Hardware Base - Abdullaeva Dilnovoz Khusniddinovna; Yuldoshev Mirzobek Nurilloevich; Ergashev Doston Radzhabovich (International Journal on Human-Computing Studies, 2021)
The article describes the possibilities of using hardware tools for implementation of a logical control task, security control, input and output of volumetric data, device interaction, as well as the possibility of using available real-time operational systems.